Association of corneal nerve loss with markers of axonal ion channel dysfunction in type 1 diabetes. Issue 1 (January 2020) - Tummanapalli, Shyam Sunder; Issar, Tushar; Kwai, Natalie; Poynten, Ann; Krishnan, Arun V.; Willcox, Mark; Markoulli, Maria
Highlights: Corneal nerve fiber loss is associated with early markers of axonal dysfunction in type 1 diabetes. Corneal nerve changes are part of a generalized neuropathic process in type 1 diabetes. In vivo corneal confocal microscopy is a potential maker of early nerve damage in DPN. Abstract: Objective: Corneal confocal microscopy (CCM) has been identified as a non-invasive technique to assess corneal nerve fiber morphology. It is not known how corneal nerve changes relate to measures of peripheral nerve function in diabetic peripheral neuropathy (DPN). The present study investigates the relationship between nerve structure and function in DPN. Methods: Fifty participants with type 1 diabetes (T1DM) and 29 healthy controls underwent CCM to assess corneal nerve fiber density (CNFD), branch density (CNBD), fiber length (CNFL), total branch density (CTBD), nerve fractal dimension (CNFrD) and inferior whorl length (IWL). The severity of DPN was assessed as Total Neuropathy Score (TNS). Motor nerve axonal excitability tests were conducted to assess axonal function. Results: Significant correlations were noted between CNFD (rho = −0.783; P  < 0.01) or superexcitability (rho = 0.435; P  < 0.01) and TNS. CNFrD was significantly correlated with peak response to stimulus ( r  = 0.414; P  < 0.01) and superexcitability ( r  = −0.467; P  < 0.01) measurements. Conclusion: Corneal nerve loss demonstrates a significant association with axonal ion channel dysfunction in T1DM. Significance: Detection of altered corneal nerve morphology may lead to the earlier diagnosis of DPN.